If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10y + -11 = -2 Reorder the terms: -11 + -10y = -2 Solving -11 + -10y = -2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -10y = -2 + 11 Combine like terms: -11 + 11 = 0 0 + -10y = -2 + 11 -10y = -2 + 11 Combine like terms: -2 + 11 = 9 -10y = 9 Divide each side by '-10'. y = -0.9 Simplifying y = -0.9
| (6a-5b+c-7d)7= | | 17x-8=12x-13 | | -6y-1=-5y-3 | | 4x-2=-18 | | 5x^2=2-9 | | 1/2y=3 | | b^2+8b+15= | | 2x-3/6-8-x/9=x+3/18 | | 6x12/36 | | 1/6X+2/3 | | 2r^2-2/3r=0 | | (N+9)=3n+27 | | 12.257x+1.9333=281.4 | | 9z-9-2z+2=0 | | y=8x+21.8 | | 6v^2-9=0 | | y=3ac | | 4(X-5/2)^2=49 | | -3(2a-4)+10a=-8 | | x+6/2-5+x/3=2-x/6 | | 2/15X+1/3 | | 4(b+1)-5=4b-1 | | 16=11/12x | | -2500-200x=-4900 | | 4(2m-5)+7m=25 | | x*x+6x-7=0 | | -60/4 | | 9ln(4x)=36 | | 2(X+9)/3=X-8 | | s/-51=-459 | | 12x-19=77 | | 12x-6(x+5)=18 |